Representation of Family Communication Patterns in Shaping Children's Personality in the Cartoon “Keluarga Pak Somat” Episode 41 - Sari, Yulia Indah Permata; Zuhriah, Zuhriah (Program Pascasarjana UIN Sumatera Utara, 2025)
Family communication patterns are represented in the cartoon “Keluarga Pak Somat” Episode 41, along with their impact on the formation of children's personality. This local cartoon serves as a significant object of study as it reflects the realities of family life within Indonesian society. This research employs a qualitative approach using Roland Barthes’ semiotic analysis method to identify the denotative, connotative, and mythological meanings of the communication patterns depicted. The findings indicate that the cartoon portrays democratic, permissive, and authoritarian communication patterns in the relationships among family members and their influence on character development in children. The cartoon implicitly conveys an educational message about the importance of healthy and positive family communication in shaping a child’s personality.